State-of-the-art responses on augmented reality application in Malaysia - Mohd Lazim, Nur Aniza; Abd Rahman, Khairul Aidil Azlin (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
This research was conducted to accumulate the awareness, perception, interest and simulation excitement responses from Malaysian public respondents in the presence of AR (Augmented Reality) in Malaysia. The keyword used was user experience, usability and perception. The terms of Augmented Reality was quite an alien to Malaysian, respondents has witness samples in order to introduce the why, where, when and how AR works. Affinity Diagram such as brainstorming, keywords extract and gathering was held from various samples of AR videos using Youtube and Vimeo applications in order to form a solid survey and proper understandable term and language for layman understanding. The survey has been constructed as simple and understandable sentences to approach respondents, that is layman user. The data is used as a preliminary data to determine the design process of Augmented Reality visual interface in order to create persuasive effect of the visual usage in Augmented Reality Application in Malaysia.